Phytochemical Comparison of the Water and Ethanol Leaf Extracts of the Cree medicinal plant, Sarracenia purpurea L. (Sarraceniaceae) - Carolina Cieniak; Brendan Walshe-Roussel; Rui Liu; Asim Muhammad; Ammar Saleem; Pierre S Haddad; Alain Cuerrier; Brian C Foster; John T Arnason (Frontiers Media S.A., 2015)
Purpose: The Cree of Eeyou Istchee in Northern Quebec identified Sarracenia purpurea L. as an important plant for the treatment of Type 2 diabetes. Traditionally the plant is used as a decoction (boiling water extract) of the leaf, however, in order to study the extract in a laboratory setting, an 80% ethanol extract was used. In this study, the phytochemistry of both extracts of the leaves was compared and quantified. Methods: Two S. purpurea leaf extracts were prepared, one a traditional hot water extract and the other an 80% ethanol extract. Using UPLC-ESI-MS, the extracts were phytochemically compared for 2 triterpenes, betulinic acid and ursolic acid, using one gradient method and for 10 additional substances, including the actives quercetin-3-O-galactoside and morroniside, using a different method. Results: The concentrations of the nine phenolic substances present, as well as an active principle, the iridoid glycoside morroniside, were very similar between the two extracts, with generally slightly higher concentrations of phenolics in the ethanol extract as expected. However, two triterpenes, betulinic acid and ursolic acid, were 107 and 93 times more concentrated, respectively, in the ethanol extract compared to the water extract. Conclusion: The main phytochemical markers and most importantly the antidiabetic active principles, quercetin-3-O-galactoside and morroniside, were present in similar amounts in the two extracts, which predicts similar bioactivity. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.